Karakteristik Pedagang Buah Di Pasar Bersehati Manado - Sumampouw, Mario; Manginsela, Elsje Pauline; Talumingan, Celcius (AGRI-SOSIOEKONOMI, 2023)
This research aims to analyze the characteristics of traders in Bersehati Market, Manado City. The research was conducted for three months from October to December 2022 from preparation to preparation of research reports. The research place is Bersehati Market, Manado City. The data collection method used in this research is primary data obtained from the research field, namely to fruit traders in Bersehati Market, Manado City by direct interview to traders using a list of questions (questionnaire). Secondary data obtained from the market office, literature and journals related to the research. The research sampling method used purposive sampling technique to fruit traders in Bersehati Market, Manado City which was taken as many as 15 respondents. The data analysis method used in the study used qualitative analysis. The results showed that the characteristics of fruit traders in Pasar Bersehati Manado City included traders aged between 21 years and 60 years, the gender of fruit traders was dominated by female traders, the last education of fruit traders was elementary school (SD) to senior high school (SMA) and equivalent, the number of dependents owned by traders was 1 to 5 family members, the capital of fruit traders varied from Rp1,000,000 to more than Rp3,000,000. The working hours of fruit traders vary from 10 working hours to 16 working hours, and the trading experience of fruit traders ranges from 1 year of work experience to the longest 30 years of work experience.